Chronique rimée de Livonie - Buschinger, Danielle; Olivier, Mathieu (2019)
"Published for the first time in French, this anonymous chronicle, composed in Middle High German at the end of the 13th century, tells the story of the conquest of Livonia, a territory in the Eastern Baltic region, by the Knights of Sword and their successors of the Teutonic order"–Translated from publisher's website